PENGEMBANGAN KUALITAS PENDIDIKAN MELALUI PROGRAM GURU PENGGERAK - Miskiyah, Azah Zakiyatul; Izzati, Umi Anugerah; Karwanto, Karwanto (Universitas Islam Negeri Alauddin Makassar, 2024)
This article explains how to improve teacher quality, namely through a teacher mobilization program. The method used uses a qualitative approach using literature reviews in the form of journals and books. In the current era, teachers are expected to be able to develop their abilities and skills in the field of education so that the teaching and learning process can provide quality education for students and produce quality students too. There are four competency standards for driving teachers, including: (1) Pedagogical competency; (2) Personality competency; (3) Professional competence; and (4) Social competence. Driving teachers have an important role in creating a learning atmosphere that can attract and motivate students to be able to develop their talents and potential independently. The aim of having a driving teacher is to provide motivation for students to improve their academic achievement, develop critical thinking skills, and also foster their own creativity. The results of the research show that the teacher mobilization program is a solution to various problems, the main one being educational equality, with this program being able to improve the quality of teachers both in urban and rural areas.